HUBUNGAN MEROKOK DENGAN KEBERSIHAN GIGI DAN MULUT PADA REMAJA DI BANJAR TUNJUK TENGAH TABANAN TAHUN 2019 - Ni Wayan Arini; AA Gede Agung; Ni Nengah Sumerti; Ary Suryo Arta (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2023)
Dental health is an integral part of general health. Dental and oral hygiene is a condition or state where the tooth are free from plaque and calculus. Smokers tend to have more plaque and tartar which results in gingivitis and is susceptible to infection. The purpose of this study was to determine the relationship between smoking and oral hygiene in adolescents at Banjar Tunjuk Tengah Tabanan in 2019. This research was an analytical study with a cross-sectional design. The teenage population is 38 people. Data were analyzed univariately and bivariately using the chi-square statistical test. The results of the study were based on the chi-square statistical test that there was no relationship between smoking duration and oral hygiene p-value = 0.122. There is a relationship between the number of cigarettes smoked per day and oral hygiene p-value = 0.000. In conclusion there is no relationship between duration of smoking and dental and oral hygiene and there is a relationship between the number of cigarettes smoked per day and oral hygiene.